2006
DOI: 10.5194/acpd-6-11817-2006
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Climatic consequences of regional nuclear conflicts

Abstract: Abstract. We use a modern climate model and new estimates of smoke generated by fires in contemporary cities to calculate the response of the climate system to a regional nuclear war between emerging third world nuclear powers using 100 Hiroshima-size bombs (less than 0.03% of the explosive yield of the current global nuclear arsenal) on cities in the subtropics. We find significant cooling and reductions of precipitation lasting years, which would impact the global food supply. The climate changes are large a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
129
2
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(149 citation statements)
references
References 25 publications
16
129
2
2
Order By: Relevance
“…Atmospheric circulation and associated changes in temperature, precipitation, and solar radiation were simulated by ModelE, a general circulation model (GCM) (Schmidt et al 2006) from the Goddard Institute for Space Studies (Robock et al 2007). For more details on the climate model results, please see Xia and Robock (2012).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Atmospheric circulation and associated changes in temperature, precipitation, and solar radiation were simulated by ModelE, a general circulation model (GCM) (Schmidt et al 2006) from the Goddard Institute for Space Studies (Robock et al 2007). For more details on the climate model results, please see Xia and Robock (2012).…”
Section: Methodsmentioning
confidence: 99%
“…The precipitation anomaly varies the most across sites, followed by temperature and radiation, as indicated by the large spread around the mean value. Robock et al (2007) showed that when averaged globally and annually, the temperature anomaly reduces to −0.5°C in year 10, but anomalies in the Midwest do not exhibit this behavior; even in year 10, the anomalies are noisy, and very cool summers still can occur.…”
Section: Expected Changes In Climatic Variablesmentioning
confidence: 99%
See 3 more Smart Citations